A possible role of FANCM mutations in male breast cancer susceptibility: Results from a multicenter study in Italy. (April 2018) - Silvestri, Valentina; Rizzolo, Piera; Zelli, Veronica; Valentini, Virginia; Zanna, Ines; Bianchi, Simonetta; Tibiletti, Maria Grazia; Varesco, Liliana; Russo, Antonio; Tommasi, Stefania; Coppa, Anna; Capalbo, Carlo; et al.
Abstract: Introduction: Breast cancer (BC) in men is a rare disease, whose etiology appears to be associated with genetic factors. Inherited mutations in BRCA1 / 2 genes account for about 10–15% of all cases. FANCM, functionally linked to BRCA1/2, has been suggested as a novel BC susceptibility gene. Our aim was to test if FANCM germline mutations could further explain male BC (MBC) susceptibility. Methods: We screened the entire coding region of FANCM in 286 MBCs by a multi-gene panel analysis, and compared these data with available whole exome sequencing data from 415 men used as population controls. Moreover, we genotyped the two most frequent FANCM mutations (c.5101C>T and c.5791C>T) in 506 MBCs and 854 healthy male controls. Results: Two FANCM truncating mutations, the c.1432C>T (p.Arg478Ter) and c.1972C>T (p.Arg658Ter), were identified in two MBC cases (0.7%). When specifically considering cases at increased genetic risk for BC, FANCM mutation frequency raises up to 1%. One mutation, the c.2201_2202delCT (p.Ser734Terfs), was found among controls (0.24%). Mutation frequency in cases was higher than in controls, however this difference was not statistically significant. FANCM c.5101C>T was not present in any of the cases and controls analyzed, whereas FANCM c.5791C>T was found in two controls (0.23%). Conclusion: Rare FANCM truncating mutations, other than c.5101C>T and c.5791C>T, may have a role in MBC susceptibility. The inclusion of FANCM in gene panels for research purpose would allow for the identification of a higher number of mutation carriers, thus helping estimate BC risk associated with FANCM mutations. Highlights: Rare FANCM mutations contribute to about 1% of high-risk male breast cancer cases. FANCM mutations were found in cases with young age of male breast cancer onset. FANCM mutations in the more 5′ region may have higher impact on BC susceptibility.